2019
DOI: 10.3390/molecules24081510
|View full text |Cite
|
Sign up to set email alerts
|

Dehydrocostus Lactone Suppresses LPS-induced Acute Lung Injury and Macrophage Activation through NF-κB Signaling Pathway Mediated by p38 MAPK and Akt

Abstract: Acute lung injury (ALI) is a severe clinical disease marked by dysregulated inflammation response and has a high rate of morbidity and mortality. Macrophages, which play diverse roles in the inflammatory response, are becoming therapeutic targets in ALI. In this study we investigated the effects of dehydrocostus lactone (DHL), a natural sesquiterpene, on macrophage activation and LPS-induced ALI. The macrophage cell line RAW264.7 and primary lung macrophages were incubated with DHL (0, 3, 5, 10 and 30 μmol/L) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
70
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(74 citation statements)
references
References 51 publications
2
70
0
Order By: Relevance
“…Although inflammation is generally recognized as a defense against various aggressions, excessive of inflammatory response leads to serious tissue damage (Lin et al, 2018). Development of ALI is due to the uncontrolled inflammation which is connected with the over-production of various inflammatory mediators produced by diversified inflammatory cells (Lee et al, 2010;Nie et al, 2019). LPS, a major element of gram-negative bacterial cell FIGURE 6 | The production of pro-inflammatory cytokines in lung tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Although inflammation is generally recognized as a defense against various aggressions, excessive of inflammatory response leads to serious tissue damage (Lin et al, 2018). Development of ALI is due to the uncontrolled inflammation which is connected with the over-production of various inflammatory mediators produced by diversified inflammatory cells (Lee et al, 2010;Nie et al, 2019). LPS, a major element of gram-negative bacterial cell FIGURE 6 | The production of pro-inflammatory cytokines in lung tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Dehydrocostus lactone 63 , also a sesquiterpene extracted from the radix of Aucklandia lappa Decne., exerted protective effects against ALI via anti-inflammatory effects. In vitro and in vivo experiments revealed that dehydrocostus lactone effectively attenuated LPS-induced pathological injury and reduced pro-inflammatory mediator expression (TNF-α, IL-6, IL-1β, iNOS, NO and IL-12) in lung and macrophages through suppressing the p38 MAPK/MK2 and Akt-mediated NF-κB signaling pathways [ 233 ].…”
Section: Natural Compounds That Exert Anti-ali Effectsmentioning
confidence: 99%
“…The site in which most dehydrocostus lactone accumulated was the lung. A recent study revealed that dehydrocostus lactone was effective in the attenuation of LPS-induced acute lung injury in mice via the inhibition of nuclear factor-κB [ 29 , 30 ]. Thus, our present results may support those of this previous study.…”
Section: Resultsmentioning
confidence: 99%